Biocompatible and hydrophilic copper-complexed polyvinyl alcohol coating for antifogging surfaces - Sivakumar Bose; Jung Seonho; Hyun Wook Kang (Polymer Testing)
Visibility is decreased when fog accumulates on the clear surface of optical devices. It is quite desirable to design the surface with antifogging properties. The current study used a dip coating process to prepare copper-incorporated polyvinyl alcohol (PVA) hydrophilic coating on the hydroxylated glass substrate. The formation of the PVA-Cu complex by the hydroxyl group was determined by FTIR and XPS methods. The surface morphology, adhesion test, wettability behavior, and cytotoxicity were investigated by SEM, cross-cut tape, contact angle measurement, and MTT experiment. By varying the CuCl2 concentration (0.0125–0.0625 M), the durability and adhesion of the coating were improved, as evidenced by its minimal mass loss and water uptake. The optimum coating condition showed a thickness of about 24.0 ± 0.7 μm and a good optical transmittance of over 90 %. Below 0.0375 M, the coating stability and water resistance could not be achieved due to the weak complexation of Cu with the PVA coating. In contrast, the PVA-Cu3 coating (0.0375 M, Cu2+ ions) was identified as an optimized condition for improved antifogging performance due to the effective complexation of Cu with the PVA matrix while maintaining the hydrophilicity and wettability behavior. Furthermore, no cytotoxicity was observed by L929 cell lines in response to the prepared coating. The current study results revealed that the adhesive, hydrophilic PVA-Cux coating with a contact angle of less than 62° might demonstrate strong antifogging properties and find its usage for endoscopic applications.